EKSPLORASI STRATEGI METAKOGNITIF UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA - Liani, Ahyani Mirah; Hamid, Abdurahman; Abidin, Muhammad Rais (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
This study aims to explore the impact of applying metacognitive strategies on students' critical thinking abilities in mathematics learning. Through a quasi-experimental design with experimental and control groups, the research involved eleventh-grade students from a secondary school in Pandeglang. Data collection methods included tests on mathematical critical thinking abilities, students' critical dispositions, and cognitive development tests using the Test of Logical Thinking (TOLT) developed by Tobin & Capie. The data were analyzed using SPSS 22.0 for Windows software. The results of the study indicate that the metacognitive approach significantly enhances students' critical thinking abilities compared to the expository approach. N-gain analysis shows a positive difference, especially in the concrete cognitive development stage. Hypothesis testing results confirm that metacognitive learning has a more positive impact on students' mathematical critical thinking abilities. With these findings, the research contributes significantly to understanding the role of metacognitive strategies in improving mathematical learning outcomes. Recommendations involve further integration of the metacognitive approach as a primary alternative in classrooms, diversification of mathematical lesson materials, and further research considering more detailed contextual variables. The implications of this research support the development of more effective and outcome-oriented pedagogy in mathematics education at the secondary level.